Cirkulär. N:o 19/1187 - Finska Statsjernvägarne (1891)
Ilmoitus lääninvankiloiden johtajien oikeudesta tilata lisävankivaunuja.
Keywords: KIERTOKIRJEET; VANKIEN KULJETUS; VAUNUT; HENKILÖVAUNUT; VANKIVAUNUT; Pienpainate